Ecscw 2001
DOI: 10.1007/0-306-48019-0_16
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Network Delays on Group Work in Real-Time Groupware

Abstract: Abstract. Network delays are a fact of life when using real-time groupware over a wide area network such as the Internet. This paper looks at how network delays affect closelycoupled group work in real-time distributed groupware. We first determine the types and amounts of delay that can happen on the Internet, and then identify typesof collaborative interactions that are affected by delay. We then examine two interaction types more closely: predicting others' movements, and coordinating shared access to artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 13 publications
2
47
0
1
Order By: Relevance
“…User studies have shown that jitter leads to a further decrease in productivity and an increase in user errors. 12 In addition to physical-layer transmission delays and end-to-end software path lengths, technologies such as firewalls, virtual private networks and other overlay networks, and lossy wireless networks add latency and other hurdles. While our simulation does not model these factors, their inclusion would have further biased our results against thin clients.…”
Section: Discussionmentioning
confidence: 99%
“…User studies have shown that jitter leads to a further decrease in productivity and an increase in user errors. 12 In addition to physical-layer transmission delays and end-to-end software path lengths, technologies such as firewalls, virtual private networks and other overlay networks, and lossy wireless networks add latency and other hurdles. While our simulation does not model these factors, their inclusion would have further biased our results against thin clients.…”
Section: Discussionmentioning
confidence: 99%
“…Work in the area of system response time suggests that delays in the range of 80-100 ms will not be noticeable by the majority of users. In a study by Mauve et al [2004] users did not notice network lags below 120 ms, thus, depending on the applications, tolerable latencies might be even higher than 80-100 ms. Gutwin [2002] showed that in a simple coordination task a delay of 200 ms already significantly increased the error rates. However, the examples used in such studies are primarily targeting humanmachine interaction or manipulation of objects and do not address the issue of self-perception and self-monitoring.…”
Section: R2: Low Latency and High Frame Ratementioning
confidence: 99%
“…Delay is a fact of life in real-world distributed applications because information must be transmitted across a network and processed at the other end before it can be displayed [9]. There are two main types of delay: latency and jitter.…”
Section: Network Delay and Its Effects On Collaborationmentioning
confidence: 99%